3(5-2x)+2x=15-4x

Simple and best practice solution for 3(5-2x)+2x=15-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5-2x)+2x=15-4x equation:


Simplifying
3(5 + -2x) + 2x = 15 + -4x
(5 * 3 + -2x * 3) + 2x = 15 + -4x
(15 + -6x) + 2x = 15 + -4x

Combine like terms: -6x + 2x = -4x
15 + -4x = 15 + -4x

Add '-15' to each side of the equation.
15 + -15 + -4x = 15 + -15 + -4x

Combine like terms: 15 + -15 = 0
0 + -4x = 15 + -15 + -4x
-4x = 15 + -15 + -4x

Combine like terms: 15 + -15 = 0
-4x = 0 + -4x
-4x = -4x

Add '4x' to each side of the equation.
-4x + 4x = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 24n=-12-12 | | 19+0.55=95.30 | | 3x^2-6x+4=3 | | 2x+x+4=8x-5x+4 | | -24-x=6 | | n/n+12=9/12 | | -3a+6(7a-1)=189 | | 16y-12y=20 | | 6x+36=54 | | 3(x+4)=8x+7-5x+5 | | x^2+3y^2-6x+6y=0 | | 12x+4=13x+-5 | | e/12+25=29 | | 2.5(x+2)+4.5+15(x-3)=15 | | 6/4x+1/2=4/9-1/7x+4/9 | | 5.4+a=7.5 | | 8x-9y=96 | | 9x21/6 | | -66=-3+7n | | 7x-8=10x-7x+8 | | 3(x+9)=9(9+x) | | 21-6t=7(t-3) | | -108=-4+2(-6b-4) | | -m^2+14m-48= | | 3(-7-3x)=78 | | (-3)+(-8)-(-2)= | | 12.6x-3.5x=182 | | 68+g=95 | | -15=(x+8)/-3 | | 2j-4j+3= | | d-13=16 | | 4(2-c)=3(c-4) |

Equations solver categories